The Basic Components of Agreement - Baumtrog, Michael D. (Informal Logic, 2023)
Disagreement has garnered attention in a variety of academic disciplines, but its counterpart agreement is deserving of much more attention than it has received. This paper begins by reviewing some of the existing literature directly discussing agreement. Inspired by these conversations, I then provide a typology of basic types of agreement followed by a more general discussion of its nature. The aim of the paper is to provide conceptual clarifications and a framework for discussing and analyzing agreement wherever it may be found.